2019
DOI: 10.1155/2019/8131235
|View full text |Cite
|
Sign up to set email alerts
|

The Application of CA and PCA to the Evaluation of Lipophilicity and Physicochemical Properties of Tetracyclic Diazaphenothiazine Derivatives

Abstract: The subject of the study was 11 new synthetized tetracyclic diazaphenothiazine derivatives. Using thin-layer chromatography in a reverse phase system (RP-TLC), their RM0 lipophilicity parameter was determined. The mobile phase was composed of 0.2 M Tris buffer (pH = 7.4) and acetone (POCH S.A., Gliwice, Poland) in different concentrations. Using computer programs, based on different computational algorithms, theoretical values of lipophilicity (AClogP, ALOGP, ALOGPs, miLogP, MLOGP, XLOGP2, and XLOGP3) as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Although it has been observed that Clog P values generated from different computer programs differ from the experimentally determine log P , often with a difference of more than 0.5 units; there however exist a strong correlation (r > 0.6) between computer generated Clog P values and experimentally determine log P . This evidence makes Clog P values a usable guide in early hit finding [ 60 ]. Herein, we generated Clog P values using ACD/Chemsketch freeware version 12.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been observed that Clog P values generated from different computer programs differ from the experimentally determine log P , often with a difference of more than 0.5 units; there however exist a strong correlation (r > 0.6) between computer generated Clog P values and experimentally determine log P . This evidence makes Clog P values a usable guide in early hit finding [ 60 ]. Herein, we generated Clog P values using ACD/Chemsketch freeware version 12.0.…”
Section: Resultsmentioning
confidence: 99%
“…Trypanosoma brucei brucei 427 trypomastigotes were cultured in iscove’s modified Dulbecco’s medium (IMDM; Lonza, Basel, Switzerland) supplemented with 10% fetal calf serum, HMI-9 supplement [ 68 ], hypoxanthine and penicillin/streptomycin at 37 °C in a 5% CO 2 incubator. Serial dilutions of test compounds were incubated with the parasites in 96-well plates for 24 h and residual parasite viability in the wells determined as previously reported [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…In practice, reaction products with a 1,2,3-triazole group in position 4 of the phenothiazine system (see Figure 1B) were synthesized and characterized [27]. The details of the preparation of quinobenzothiazinium derivatives that revealed their noteworthy biological properties were presented in our previous reports [28][29][30]. The direction and strength of the antibacterial and anticancer activity depended on the presence and nature of the substituents in the tetracyclic quinobenzothiazinium system.…”
Section: Introductionmentioning
confidence: 99%
“…Lipophilicity, defined as the affinity of a compound towards nonpolar phase, is also significant for potential drug evaluation [ 29 ]. The log P parameter is linked to the absorption, distribution, metabolism and excretion processes [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%